2008
DOI: 10.2967/jnumed.108.054379
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a Mean Transit Time Measurement with an Acetazolamide Test Increases Predictive Power to Identify Elevated Oxygen Extraction Fraction in Occlusive Carotid Artery Diseases

Abstract: Reduced cerebral blood flow and cerebrovascular reactivity to acetazolamide have been used as predictors for subsequent ischemic stroke in patients with occlusive carotid artery diseases, called type 3 ischemia. However, recent studies have shown that reduced cerebrovascular reactivity to acetazolamide does not always represent elevated oxygen extraction fraction (OEF). The aim of this study was to establish the methodology to improve the validity of an acetazolamide test identifying elevated OEF. Methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
(49 reference statements)
3
7
0
Order By: Relevance
“…Although using the combination of CBF and CVR also improves the accuracy in detecting an elevated OEF, this effect is not sufficient. 9 Our data obtained using the 123 I-IMP-autoradiography method with SPECT corresponded to previous findings obtained using PET.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although using the combination of CBF and CVR also improves the accuracy in detecting an elevated OEF, this effect is not sufficient. 9 Our data obtained using the 123 I-IMP-autoradiography method with SPECT corresponded to previous findings obtained using PET.…”
Section: Discussionsupporting
confidence: 77%
“…[7][8][9]30 Although most patients without reduced CBF or CVR have a normal OEF, only half of the patients with reduced CBF or CVR have an elevated OEF. Although using the combination of CBF and CVR also improves the accuracy in detecting an elevated OEF, this effect is not sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…We found that OEF was significantly elevated in the hemisphere ipsilateral to the stenotic or occluded artery compared with the contralateral hemisphere, consistent with previous studies. 4,5,[17][18][19] This finding suggested the hemodynamic impairment in the hemisphere ipsilateral to the vascular lesion.…”
Section: Discussionmentioning
confidence: 77%
“…They suggested that increased cerebral blood volume could indicate autoregulatory vasodilatation in response to cerebral perfusion pressure reduction and predict an increased oxygen ejection fraction in patients with adult MMD, on the basis of previous studies in patients with carotid occlusive disease. [22][23][24] Several parameters have been suggested to predict postoperative hyperperfusion, which includes as yet unexplained postoperative transient neurological deterioration associated with normalized or unchanged CBF on postoperative SPECT compared to preoperatively. In the present study, postoperative transient neurological deterioration was accurately predicted using Youden index.…”
Section: Discussionmentioning
confidence: 99%